THE EFFECT OF SPECIALIZED AMINO ACIDS ON THE DETOXIFICATION FUNCTION OF THE LIVER IN ACUTE DIFFUSE PERITONITIS - Gaziev Z.T., Saparniyazov N.S. (Central Asian Journal of Medicine, 2025)
The article presents the results of a prospective clinical and laboratory study aimed at assessing the effect of specialized amino acid solutions on the liver detoxification function in patients with acute diffuse peritonitis. Biochemical parameters (ALT, AST, bilirubin, albumin), plasma ammonia levels and the results of the caffeine test as a marker of liver microsomal activity were studied. It was shown that the use of amino acids (including ornithine, arginine, glutamine and BCAA) leads to a reliable improvement in the synthetic and detoxification function of the liver, acceleration of xenobiotic metabolism and a decrease in endogenous intoxication. The results confirm the advisability of including amino acid support in the complex therapy of acute surgical conditions accompanied by liver dysfunction.